Islamic Boarding School as an Ecosystem for Religious Moderation Education in The Madura Society - Mas'udi, Mas'udi; Muflihah, Muflihah (EDUKASIA, 2023)
This research is directed at discussing the emerging religious education ecosystem in Madurese society. Throughout its journey, Islamic boarding schools have become an integral part of Madurese society, encompassing social, cultural, religious, political, and economic aspects. To assemble all the codified data necessary to communicate the primary objective of this research, interviews, observations, and documentation were utilized as data collection sources. Subsequently, the study analysis was formulated descriptively, employing a cultural anthropological approach. Through comprehensive analysis in research, it was revealed that the religious moderation education system in Madurese society occurs on the basis of cultural openness. The openness in Islamic boarding school life is fostered by the social, cultural, and political aspects that evolve and establish a tradition. The togetherness of life in Islamic boarding schools serves as the main benchmark for embracing the presence of others as fellow brothers, comprising social, cultural, and political dimensions.